2018
DOI: 10.4212/cjhp.v71i2.1861
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Clinical Pharmacist Handover Process in the Intensive Care Unit with a Pharmacotherapy-Specific Tool: The I-HAPPY Study

Abstract: <p><strong>ABSTRACT</strong></p><p><strong>Background: </strong>Pharmacists in the intensive care unit (ICU) provide pharmaceutical care to critically ill patients. Identification and resolution of drug therapy problems improves outcomes for these patients. To maintain continuity of care, pharmacotherapy plans should be transferred to a receiving pharmacist upon discharge of patients from the ICU. No previous studies have addressed the development or evaluation of a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, this model places higher demand on staffing and skill mix within a hospital pharmacy department. There is a paucity of published literature describing the effectiveness of pharmacist-specific handover tools and processes (202). Phase Five concluded that, alongside their clinical outcomes, key economic metrics such as the cost and cost savings of the service must be captured in future research, and a comparator group must be included.…”
Section: Pharmacist Contributionsmentioning
confidence: 99%
“…However, this model places higher demand on staffing and skill mix within a hospital pharmacy department. There is a paucity of published literature describing the effectiveness of pharmacist-specific handover tools and processes (202). Phase Five concluded that, alongside their clinical outcomes, key economic metrics such as the cost and cost savings of the service must be captured in future research, and a comparator group must be included.…”
Section: Pharmacist Contributionsmentioning
confidence: 99%